2014
DOI: 10.4314/ejb.v16i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-intestinal helminths of pigeons (<i>Columba livia</i>) in Gujarat, India</i>

Abstract: A study was conducted to assess the prevalence of helmith parasites of domestic wild and zoo pigeons in Gujarat, India by faecal sampling and postmortem examination. Qualitative examination of 78 faecal samples revealed 71 (91%) with parasitic infections of nematodes (85%), cestodes (31%) and Eimeria sp (77%). There were 200-1600 nematode eggs per gram during the monsoon season, which was high compared to the 200-1000 eggs per gram in winter and summer. In post-mortems 85% had parasitic infections, of nematode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
4
7
0
Order By: Relevance
“…The prevalence rate of Eimeria spp. 6(8.1%) (Figure 8) in this study and similar with Sivajothi et al (2014), while (Parsani et al, 2014) (Saleem et al, 2016, Sürsal et al, 2017 reported that the prevalence of this blood parasite was higher than that found in this study. Also (Samani et al, 2013) found a prevalence of 24% in Southwest Iran.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence rate of Eimeria spp. 6(8.1%) (Figure 8) in this study and similar with Sivajothi et al (2014), while (Parsani et al, 2014) (Saleem et al, 2016, Sürsal et al, 2017 reported that the prevalence of this blood parasite was higher than that found in this study. Also (Samani et al, 2013) found a prevalence of 24% in Southwest Iran.…”
Section: Discussionsupporting
confidence: 85%
“…Authors in different countries also worked on the prevalence of Raillietina tapeworm in pigeons and recorded lower or higher prevalence rate than reported in the present study. Mehmood et al (2019) in India recorded 25% prevalence, Safi-Eldin et al (2019) in Cairo, Egypt recorded 24.79% prevalence, Mohammed et al (2019) in Kano State, Nigeria recorded 13.80% prevalence, El-Dakhly et al (2019) in Aswan, Egypt recorded 43.33% prevalence, Sadeghi-Dehkordi et al (2019) in Hamedan, Iran recorded 20% prevalence, Chaechi-Nosrati et al (2018) in Lahijan, Guilan, Iran recorded 54.5% prevalence, Alkharigy et al (2018) in Tripoli, Libya recorded 35% prevalence, Umaru et al (2017) in Taraba State, Nigeria recorded 18.3% prevalence, Parsani et al (2014) in Gujrat, India recorded 31% prevalence. In contrast, Al Quraishy et al (2019) in Saudi Arabia recorded 77.78% prevalence, Diakou et al (2013) in Thessaloniki, Nothern Greece recorded 70.58% prevalence.…”
Section: Discussionmentioning
confidence: 97%
“…Many health issues can affect pigeons, but infestations with parasites play an essential part. Many ecto- and endoparasites, associated with several pigeon diseases, are found on the skin and various internal organs ( Parsani et al, 2014 ). Helminths have been involved in causing infection and higher mortality in domestic pigeons.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the prevalence of intestinal parasites in the pigeons was analysed in the current study. The prevalence rate (87.1%) was lower than the findings from previous studies among feral pigeons from Nepal (90.83%; n = 120) (Jha, 2017), Bangladesh (100%; n = 60) (Begum & Sehrin, 2013), Poland (100%; n = 90) (Balicka‐Ramisz et al., 2021) and India (91%; n = 78) (Parsani et al., 2014) and higher than the findings from Iran (79.2%; n = 250) (Bahrami et al., 2013), Brazil (74.14%; n = 58) (Tietz Marques et al., 2007), India (72.7%; n = 132) (Sivajothi & Sudhakara, 2015), Pakistan (73.33%; n = 210) (Baber et al., 2020) and (60%, n = 30) (Yousafzai et al., 2021), Bangladesh (70.76%; n = 65) (Islam et al., 2017), Nepal (69.16%; n = 120) (Gurung, 2016), Turkey (59.6%; n = 136) (Sari et al., 2008) and Libya (56%; n = 100) (Alkharigy et al., 2018). The variation in these results might be attributed to the sampling techniques, the sampling size, the examination methods, the detected parasites and the ecology of sampling geographies.…”
Section: Discussionmentioning
confidence: 55%
“…90.83%; n = 120)(Jha, 2017), Bangladesh (100%; n = 60)(Begum & Sehrin, 2013), Poland (100%; n = 90)(Balicka-Ramisz et al, 2021) and India (91%; n = 78)(Parsani et al, 2014) and higher than the findings from Iran (79.2%; n = 250)(Bahrami et al, 2013), Brazil (74.14%; n = 58) (TietzMarques et al, 2007), India (72.7%; n = 132)(Sivajothi & Sudhakara, 2015), Pakistan (73.33%; n = 210)(Baber et al, 2020) …”
mentioning
confidence: 99%